Aplicación web para la gestión de información en la liga barrial santa Ana de Tanicuchi. - Quishpe Farinango, Carlos Ignacio (2019)
The technological proposal was developed in the Santa Ana neighborhood league of the rural Parish Tanicuchi in Latacunga Canton, Cotopaxi Province, to design and implement a web application that simplifies the organizational processes of the various sporting championships, which during the year makes the league. Nowadays, soccer is the source of fraternity among people, being common to observe weekends to entire families share moments of healthy recreation. The research study starts from the analysis of how the different championships are developed which neither have a planning nor an adequate follow-up empirically taking the data and results without detail that helps to control year after year if the expectations raised at the beginning of each championship are being fulfilled, the automation of the processes and of the correct collection and storage of data by means of the insertion of computer tools in the league. It generated a better performance at the moment of being able to manage the different parameters that intervene in the organization of a sport championship, benefiting in this way the directive part who manage the championships, the organizational part formed by the teams, referees, players and external personnel to the championship, achieving that the organization times decrease, as well as the organization costs, and that the information on the different championships can be better socialized with the community, being stored in a better way in a database and so it can be taken as reference regarding to statistical data for posterity.